Synergistic Catalysis by Copper Oxide/Graphene Oxide Nanocomposites: A Facile Approach to Prepare Quinazolines and Quinazoline Containing Triazole/Tetrazole Moieties under Mild Reaction Conditions. Issue 22 (9th June 2022) - Sarkar, Rajib; Gajurel, Sushmita; Gupta, Ajay; Kumar Pal, Amarta
Abstract: A one‐pot three‐component strategy for the synthesis of quinazoline derivatives under catalyst‐free and using CuO/GO nanocomposite has been developed. The catalytic approach proceeded under mild reaction conditions and offered improved yields of the target products within shorter reaction time. The excellent catalytic performance of CuO/GO can be ascribed to the synergistic interaction of the combined graphene oxide (GO) and nano‐sized CuO nanoparticles. A wide variety of substrates, including aromatic, heteroaromatic, and bulky aldehydes were explored to obtain highly functionalized quinazoline products in good to high yields. Furthermore, this atom‐efficient catalytic pathway has also been extended for the synthesis of quinazoline containing triazole and tetrazole rings. Additionally, the nanocatalyst could be easily recycled and reused five times without much appreciable loss in its activity. Abstract : We presented the synthesis of a library of quinazoline derivatives under catalyst‐free and using CuO/GO nanocomposite as an efficient heterogeneous reusable catalyst. The CuO/GO nanocatalyst was also utlilized for the preparation of quinazoline containing triazole/tetrazole moieties. The excellent catalytic performance of CuO/GO nanocomposite can be ascribed to the synergistic interaction between GO and CuO nanoparticles. Mild reaction conditions, high substrate scope, short reaction time, and easy recyclability of the catalyst are some of the attractive features of the present methodology.